Regional analysis of convective systems during the West African monsoon - Guy, Bradley Nicholas, author; Rutledge, Steven, advisor; Tao, Wei-Kuo, advisor; Kummerow, Christian, committee member; van den Heever, Sue, committee member; Cifelli, Rob, committee member; Reising, Steven, committee member (Colorado State University. Libraries, 2012)
The West African monsoon (WAM) occurs during the boreal summer and is responsible for a majority of precipitation in the northern portion of West Africa. A distinct shift of precipitation, often driven by large propagating mesoscale convective systems, is indicated from satellite observations. Excepting the coarser satellite observations, sparse data across the continent has prevented understanding of mesoscale variability of these important systems. The interaction between synoptic and mesoscale features appears to be an important part of the WAM system. Without an understanding of the mesoscale properties of precipitating systems, improved understanding of the feedback mechanism between spatial scales cannot be attained. Convective and microphysical characteristics of West African convective systems are explored using various observational data sets. Focus is directed toward meso -α and -β scale convective systems to improve our understanding of characteristics at this spatial scale and contextualize their interaction with the larger-scale. Ground-based radar observations at three distinct geographical locations in West Africa along a common latitudinal band (Niamey, Niger [continental], Kawsara, Senegal [coastal], and Praia, Republic of Cape Verde [maritime]) are analyzed to determine convective system characteristics in each domain during a 29 day period in 2006. Ancillary datasets provided by the African Monsoon Multidisciplinary Analyses (AMMA) and NASA-AMMA (NAMMA) field campaigns are also used to place the radar observations in context. Results show that the total precipitation is dominated by propagating mesoscale convective systems. Convective characteristics vary according to environmental properties, such as vertical shear, CAPE, and the degree of synoptic forcing. Data are bifurcated based on the presence or absence of African easterly waves. In general, African easterly waves appear to enhance mesoscale convective system strength characteristics (e.g. total precipitation and vertical reflectivity profiles) at the inland and maritime sites. The wave regime also resulted in an increased population of the largest observed mesoscale convective systems observed near the coast, which led to an increase in stratiform precipitation. Despite this increase, differentiation of convective strength characteristics was less obvious between wave and no-wave regimes at the coast. Due to the propagating nature of these advecting mesoscale convective systems, interaction with the regional thermodynamic and dynamic environment appears to result in more variability than enhancements due to the wave regime, independent of location. A 13-year (1998-2010) climatology of mesoscale convective characteristics associated with the West African monsoon are also investigated using precipitation radar and passive microwave data from the NASA Tropical Rainfall Measuring Mission satellite. Seven regions defined as continental northeast and northwest, southeast and southwest, coastal, and maritime north and south are compared to analyze zonal and meridional differences. Data are categorized according to identified African easterly wave (AEW) phase and when no wave is present. While some enhancements are observed in association with AEW regimes, regional differences were generally more apparent than wave vs. no-wave differences. Convective intensity metrics confirm that land-based systems exhibit stronger characteristics, such as higher storm top and maximum 30-dBZ heights and significant 85-GHz brightness temperature depressions. Continental systems also contain a lower fraction of points identified as stratiform. Results suggest that precipitation processes also varied depending upon region and AEW regime, with warm-rain processes more apparent over the ocean and the southwest continental region and ice-based microphysics more dominant over land, including mixed-phase processes. AEW regimes did show variability in stratiform fraction and ice and liquid water content, suggesting modulation of mesoscale characteristics possibly through feedback with the synoptic environment. Two mesoscale convective systems (MCSs) observed during the African Monsoon Multidisciplinary Analyses (AMMA) experiment are simulated using the three-dimensional (3D) Goddard Cumulus Ensemble model. One of the MCSs, the 8 September 2006 system, is associated with the passage of an African easterly wave trough while the other, the 14 July 2006 case, is not. Simulations are performed using 1 km horizontal grid spacing, a lower limit on current embedded cloud resolving models within a multi-scale modeling framework. Simulated system structure is compared to radar observations using contoured frequency-by-altitude diagrams (CFADs), calculated ice and water mass, and identified hydrometeor variables. Results indicate general agreement in the temporal distribution of hydrometeors. Vertical distributions show that ice hydrometeors are often underestimated at mid- and upper-levels, partially due to the inability of the model to produce adequate system heights. Abundance of high reflectivity values below and near the melting level in the simulation led to a broadening of the CFAD distributions. Observed vertical reflectivity profiles indicate larger reflectivities aloft compared to simulated values. Despite these differences and biases, the radar-observed differences between the two cases are noticeable in the simulations as well, suggesting that the model is able to capture gross observed differences between the two MCSs.
Keywords: mesoscale convective systems; African easterly waves; precipitation; regional convection; West African monsoon; microphysics